An improved replacement oscillator approach for soil-structure interaction analysis considering soft soils. (15th July 2018) - Lu, Yang; Hajirasouliha, Iman; Marshall, Alec M.
Highlights: Absolute acceleration spectra should be used for EFSDOF oscillators. EFSDOF oscillators overestimate Rμ values for heavily damped SSI systems. Response of SSI systems relates to the predominant period of soft soil records. EFSDOF oscillators were improved to consider heavy damping and soft soils. Abstract: This paper aims to improve the effectiveness of the replacement oscillator approach for soil-structure interaction (SSI) analysis of flexible-base structures on soft soil deposits. The replacement oscillator approach transforms a flexible-base single-degree-of-freedom (SDOF) structure into an equivalent fixed-base SDOF (EFSDOF) oscillator so that response spectra for fixed-base structures can be used directly for SSI systems. A sway-rocking SSI model is used as a baseline for assessment of the performance of EFSDOF oscillators. Both elastic and constant-ductility response spectra are studied under 20 horizontal ground motion records on soft soil profiles. The effects of frequency content of the ground motions and initial damping of the SSI systems are investigated. It is concluded that absolute acceleration spectra, instead of pseudo-acceleration spectra, should be used for EFSDOF oscillators in force-based design of SSI systems. It is also shown that using an EFSDOF oscillator is not appropriate for predicting the constant-ductility spectra when the initial damping ratio of the SSI system exceeds 10%. Based on the results of this study, a correction factor is suggested to improve the accuracy of the replacement oscillator approach for soft soil conditions.